Functional electrical stimulation (FES) of the upper limb alleviates unilateral neglect: a case series analysis. - Harding, P; Riddoch, M (2009)
We report the results of a new form of therapy for unilateral spatial neglect. Functional electrical stimulation (FES) applied to the left forearm extensor muscles reduced the symptoms of severe left unilateral visual neglect in three patients, with the benefits being measurable at 6 months post-treatment. We suggest that FES activates a proprioceptive map within the right parietal lobe whose level of activation is otherwise diminished by the lesion. This both increases awareness of the contralesional side and stimulates functional interactions with the environment.